2006
DOI: 10.1590/s0073-47212006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Associative learning in wild Anastrepha obliqua females (Diptera, Tephritidae) related to a protein source

Abstract: ABSTRACT. The aim of the present study was to determine whether wild adult Anastrepha obliqua (Macquart, 1835) females are able to associate a compound (quinine sulphate -QS) not related to their habitual diet with a protein-enriched food. Females were first fed on diets based on brewer yeast and sucrose containing or not QS. The groups were then allowed to choose between their original diets and a diet with or without QS, depending on the previous treatment, and between a diet based on agar and a diet contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 18 publications
(17 reference statements)
0
15
2
Order By: Relevance
“…The stimulating effect of novelty, in this context, would also explain the significant difference that was found on the first day of selection, once this was the first day that females had contact with the Y substrate. The results found in this present study differ from the ones found in the study by Cresoni-Pereira and Zucoloto (2006), where associative learning related to A. obliqua feeding behavior was studied. When the diets for choice had an adequate nutritional value, the flies did not show any preference for the diet with yeast + quinine sulphate or the diet containing only yeast.…”
Section: Day Of Selectioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The stimulating effect of novelty, in this context, would also explain the significant difference that was found on the first day of selection, once this was the first day that females had contact with the Y substrate. The results found in this present study differ from the ones found in the study by Cresoni-Pereira and Zucoloto (2006), where associative learning related to A. obliqua feeding behavior was studied. When the diets for choice had an adequate nutritional value, the flies did not show any preference for the diet with yeast + quinine sulphate or the diet containing only yeast.…”
Section: Day Of Selectioncontrasting
confidence: 99%
“…The five-day period of experience was based on previous studies about associative learning related to the A. obliqua feeding behavior (Cresoni-Pereira & Zucoloto, 2006).…”
Section: Day Of Selectionmentioning
confidence: 99%
See 3 more Smart Citations